2019
DOI: 10.21203/rs.2.10393/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of intraoperative lidocaine versus esmolol infusion on postoperative analgesia in laparoscopic cholecystectomy: A randomized clinical trial

Abstract: Background: As a part of multimodal analgesia for laparoscopic cholecystectomy, administration of systemic lidocaine is a well-known technique. Similarly, esmolol has been found to have an opioid sparing effect in the perioperative setting. The aim of the study was to compare opioid consumption after an intraoperative infusion of lidocaine or esmolol in female patients undergoing elective laparoscopic cholecystectomy. Methods: In this prospective, randomized, double-blind clinical trial, 90 female patients sch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…However, we expect higher bolus doses or the use of extra infusion to reduce agitation because anxiety, pain, and sympathetic activation are causes of agitation [5]. Furthermore, one study reported that esmolol reduced postoperative pain and sympathetic activation [41]. However, similar to dexmedetomidine, esmolol can cause severe bradycardia in patients undergoing eye surgery; therefore, we concluded that additional infusion of esmolol in the case of eye surgery is risky and did not use it in this study.…”
Section: Discussionmentioning
confidence: 91%
“…However, we expect higher bolus doses or the use of extra infusion to reduce agitation because anxiety, pain, and sympathetic activation are causes of agitation [5]. Furthermore, one study reported that esmolol reduced postoperative pain and sympathetic activation [41]. However, similar to dexmedetomidine, esmolol can cause severe bradycardia in patients undergoing eye surgery; therefore, we concluded that additional infusion of esmolol in the case of eye surgery is risky and did not use it in this study.…”
Section: Discussionmentioning
confidence: 91%